THE EFFECT OF EVERYONE IS A TEACHER HERE LEARNING STRATEGY ON LEARNING RESULT OF VIII CLASS ON BIOLOGY LEARNING - Berlian, Zainal; Riswanda, Jhon; Ariska, Feby; Handayani, Tutut (Al 'Ilmi : Jurnal Pendidikan MIPA, 2015)
This study aims to determine the effect of active learning strategy type everyone is a teacher here to the results of students' Biology learning. This type of research is a quantitative research. The population used is the entire class VIII in one school in Musi Banyuasin Regency which consists of three classes. The technique used is purposive sampling technique, from three classes of population are taken two classes that are used as sample of experimental class and control class that is class VIII.1 and VIII.2 with the number of students as much as 54 people. Data collection is done by giving test and questionnaire of student responses. After the data obtained from the research results then the data is analyzed by 2 ways, namely by inferential analysis techniques and n-gain. Inferential technique is used to find out the influence of active learning strategy type everyone is a teacher here on student learning outcomes. The results showed that there is a positive influence of the use of active learning strategy type of everyone is a teacher here on student learning outcomes, it can be seen from the t-test that is tcount 4,167> ttabel 1,675 and significance value 0,000<0,05, hence Ha accepted and H0 is rejected, and based on the comparison of mean values and the percentage of student learning outcomes indicates that the experimental class is superior to the control class. Keywords: active learning, everyone is a teacher here, learning strategy, learning result